2018
DOI: 10.3847/1538-4357/aaaf6b
|View full text |Cite
|
Sign up to set email alerts
|

Future Cosmological Constraints From Fast Radio Bursts

Abstract: We consider the possible observation of Fast Radio Bursts (FRBs) with planned future radio telescopes, and investigate how well the dispersions and redshifts of these signals might constrain cosmological parameters. We construct mock catalogues of FRB dispersion measure (DM) data and employ Markov Chain Monte Carlo (MCMC) analysis, with which we forecast and compare with existing constraints in the flat ΛCDM model, as well as some popular extensions that include dark energy equation of state and curvature para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 75 publications
1
77
0
1
Order By: Relevance
“…The first repeating burst FRB 121102, was localized in a star-forming dwarf galaxy at z = 0.193, which has confirmed the cosmological origin of FRBs Scholz et al 2016;Chatterjee et al 2017;Marcote et al 2017;Tendulkar et al 2017). Although the progenitors and radiation mechanism are still debated, FRBs have been proposed to be promising tools for cosmological and astrophysical studies, such as locating the "missing" baryons (Mcquinn 2014), constraining the cosmological parameters (Gao et al 2014;Zhou et al 2014;Yang & Zhang 2016a;Walters et al 2018), directly measure Ω b of the universe (Deng & Zhang 2014;Keane et al 2016) and probe the reionization history of the universe (Deng & Zhang 2014;Zheng et al 2014;Caleb et al 2019;Li et al 2019), probing compact dark matter or precisely measuring the Hubble constant and the cosmic curvature through gravitationally lensed FRBs (Muñoz et al 2016;Li et al 2018), measuring cosmic proper distances (Yu & Wang 2017), testing the Einstein's weak equivalence principle (WEP, Wei et al 2015;Nusser 2016;Tingay & Kaplan 2016;Wu et al 2017;Yu et al 2018) and constraining the rest mass of the photon Bonetti et al 2016Bonetti et al , 2017Shao & Zhang 2017).…”
Section: Introductionmentioning
confidence: 76%
“…The first repeating burst FRB 121102, was localized in a star-forming dwarf galaxy at z = 0.193, which has confirmed the cosmological origin of FRBs Scholz et al 2016;Chatterjee et al 2017;Marcote et al 2017;Tendulkar et al 2017). Although the progenitors and radiation mechanism are still debated, FRBs have been proposed to be promising tools for cosmological and astrophysical studies, such as locating the "missing" baryons (Mcquinn 2014), constraining the cosmological parameters (Gao et al 2014;Zhou et al 2014;Yang & Zhang 2016a;Walters et al 2018), directly measure Ω b of the universe (Deng & Zhang 2014;Keane et al 2016) and probe the reionization history of the universe (Deng & Zhang 2014;Zheng et al 2014;Caleb et al 2019;Li et al 2019), probing compact dark matter or precisely measuring the Hubble constant and the cosmic curvature through gravitationally lensed FRBs (Muñoz et al 2016;Li et al 2018), measuring cosmic proper distances (Yu & Wang 2017), testing the Einstein's weak equivalence principle (WEP, Wei et al 2015;Nusser 2016;Tingay & Kaplan 2016;Wu et al 2017;Yu et al 2018) and constraining the rest mass of the photon Bonetti et al 2016Bonetti et al , 2017Shao & Zhang 2017).…”
Section: Introductionmentioning
confidence: 76%
“…In particular, they could provide a good map of the baryon distribution, magnetic fields and turbulence in the IGM, helium reionization, and might serve as a new tool for measuring cosmological distances to high redshifts z 1, e.g. [21][22][23][24][25][26]. A new cosmological distance measure would be exciting, and useful, if it could be made sufficiently robust and competitive in precision to existing cosmological distance probes such as Type Ia supernovae standard candles and baryon acoustic oscillations standard rulers.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of the FRB 121102 (Chatterjee et al 2017;Marcote et al 2017;Tendulkar et al 2017) confirmed the cosmological origin of this source (at z = 0.19). If many redshifts of FRBs are measured by upcoming instruments, the combined redshift and DM can be used as cosmological purpose, including measuring the baryon number density (Deng & Zhang 2014;Keane et al 2016), measuring cosmic proper distance , constraining the cosmological parameters (Zhou et al 2014;Gao et al 2014;Walters et al 2018), measuring the Hubble Constant and cosmic curvature if some repeating FRBs are gravitationally lensed (Li et al 2018), probing compact dark matter through strong lensed FRBs (Muñoz et al 2016;) and testing ⋆ E-mail: fayinwang@nju.edu.cn Einstein's Weak Equivalence Principle (WEP) (Wei et al 2015;Yu et al 2018).…”
Section: Introductionmentioning
confidence: 99%